Tactile Map Book for Students with Visual Impairments A Step towards Inclusive Education in India - Pandey, Aparna (JOURNAL OF INDIAN EDUCATION, 2016)
The paper highlights the significance of teaching-learning of Geography to students with visual impairments with the help of tactile maps for enhancing their map reading skills. The study reveals the status of teaching-learning of Geography to visually impaired in schools and availability of teaching-learning materials in Geography for students with visual impairments in the country. The development of an innovative tactile map book based on innovative technology for students with visual impairments and their responses on the map book bring some hope for future in qualitative improvement of teaching-learning of Geography. A conscious effort has been made to develop tactile map book in view of crucial pedagogical concerns related to the subject and of the learners.